Early Detection and Prevention of Suicidal Behavior in Adolescents - Sabir Nurkhodjaev1, Sayora Babarakhimova2, Vasila Abdullaeva3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This article highlights the results of research, which help reveal high-risk groups to suicide among adolescentsbased on types of family relationships and provide timely medical, psychological and psycho-correction helpfor parents and children, predict suicidal behavior at early stages. An major role in prevention of adolescentsuicides is played by the family and healthy family relationships, as they ensure harmonious developmentof a personality.